Mauritian Coastal Algal Bloom: A Review on Occurrence, Pollution Sources and Associated Environmental and Human Health Risks - Sharma, Chummun Vedendranand; Tuppad, Pushpa; Sarvajayakesavalu, Suriyanarayanan (International Journal of Aquatic Research and Environmental Studies, 2026)
One of the emerging public health and environmental problems in coastal systems is the algal blooms which are driven by the interaction of climate variability, nutrient enrichment and hydrodynamic processes. Mauritius, a Small Island Developing State (SIDS) experiences regular algal bloom events occurring especially in the eastern coasts (Belle Mare and Palmar) and western coasts (Flic en Flac and Wolmar). Further to this, there are cumulative consequences for marine ecosystems, fisheries, tourism and human health. A comprehensive desk-based synthesis of algal bloom occurrence in Mauritian waters from 1900 to 2025 is presented in this work which integrates peer reviewed literature, environmental datasets, and observational reports. Several key drivers such as anthropogenic nutrient inputs from agriculture, wastewater discharge and urbanization, seasonal climatic factors including rainfall and sea surface temperature, changing coastal hydrodynamics especially surface runoff vs submarine groundwater discharge were identified to initiate and catalyze the process. This resulted in producing large scale seasonal blooms on the eastern coast and more persistent localized blooms on the western coast. It was also found that several algae species found in Mauritian waters can produce toxins with potential implication for seafood safety, ecosystem health and tourism sector. It was hence proposed to shift towards integrated ‘catchment to coast management’, supported by AI-based predictive monitoring and early warning systems and also embarking in the sustainable valorization of algal biomass within the circular bioeconomy framework. This study provides a national-level synthesis that supports evidence-based policymaking, strengthens monitoring strategies, and identifies priorities for future research to advance sustainable coastal management in Small Island States such as Mauritius.